2004
DOI: 10.1128/jcm.42.5.2271-2274.2004
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic and Symptomatic Excretion of Noroviruses during a Hospital Outbreak of Gastroenteritis

Abstract: During an investigation of a hospital outbreak of norovirus gastroenteritis identified as being caused by a recombinant genogroup II (rGII-3a) strain, fecal specimens collected from asymptomatic staff and patients were tested by nested PCR. A GII-4 norovirus strain, the predominant strain associated with outbreaks in hospitals over the last few years, was detected in 26 and 33% of asymptomatic staff and patients, respectively. No rGII-3a (Harrow/Mexico) norovirus strains were detected in the samples of asympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
82
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 18 publications
5
82
1
2
Order By: Relevance
“…A number of epidemiological reports on NV infection have shown that the GII genogroup is the predominant agent of NV-associated gastroenteritis (11,14,29,36). In this study, GII strains were also predominant in both sporadic cases and outbreaks.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…A number of epidemiological reports on NV infection have shown that the GII genogroup is the predominant agent of NV-associated gastroenteritis (11,14,29,36). In this study, GII strains were also predominant in both sporadic cases and outbreaks.…”
Section: Discussionmentioning
confidence: 52%
“…They are one of the most common causes of gastroenteritis and have been detected in fecal samples from both humans (12,15,28) and animals (20,30,37). Human-associated NV outbreaks resulting from ingestion of contaminated water or food, such as oysters (4,5,18,23), and outbreaks in public places, particularly hospitals, schools, and cruise ships (9,11,22,36), pose an important public health problem.Reverse transcription-PCR (RT-PCR) and sequencing of the partial viral genome are the most popular and useful procedures for obtaining epidemiological and genetic information on NVs. Human NVs can be divided into two genogroups, genogroups GI and GII, by genetic analysis of the RNA polymerase and capsid regions (1, 15), with several genotype classifications having been reported independently (1,16,33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, taken as a whole, these results have shown that asymptomatic infections were widespread in the food-catering industry in Japan at the time of the study. Recently, excretion of norovirus by symptomatic and asymptomatic individuals during a hospital outbreak of gastroenteritis where a GII/4 strain was dominant has been described (6). At present, norovirus GII/4 strains are the most prevalent in many countries (4,8,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Usually in exposed individuals, histologic lesions correlate with diarrhea, but in one report, lesions in volunteers who did not show clinical symptoms were described (42). There are also numerous reports of asymptomatic individuals who were infected with HuNoVs and shed virus in the feces (11,28).…”
mentioning
confidence: 99%